The impact of community learning program to a Kuantan dental students - Abllah, Zurainie; Sayed Kamar, Syarifah Haizan; Ab Halim, Noorhazayti; Supa'at, Salwana; Che Musa, Muhd Firdaus (Elsevier, 2019)
Community learning program is an important part in the education of medical and dental students all over the world. Final year dental students IIUM Kuantan session 2017-2018 were given a self-administered questionnaire, (N=58). All respondents agreed that they have a responsibility to serve the community and aware their role in community. 98% agreed that participating in the outreach activity made the aware of the roles in other discipline and the needs of the community. The complaints include workload and insufficient preparation time. The program positively impacted these students and enhanced their social responsibility by exposing them to the community.